2019
DOI: 10.1073/pnas.1900762116
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic plant viroid infections in phytopathogenic fungi

Abstract: Viroids are pathogenic agents that have a small, circular noncoding RNA genome. They have been found only in plant species; therefore, their infectivity and pathogenicity in other organisms remain largely unexplored. In this study, we investigate whether plant viroids can replicate and induce symptoms in filamentous fungi. Seven plant viroids representing viroid groups that replicate in either the nucleus or chloroplast of plant cells were inoculated to three plant pathogenic fungi, Cryphonectria parasitica, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 100 publications
4
55
0
Order By: Relevance
“…Nerva et al (2017) presented strong evidence to show that a virus that infects an endophytic fungus could replicate in plants. Additionally, viroids have been shown to infect fungi efficiently (Wei et al, 2019). These findings further confirmed that some mycoviruses are close relatives to plant viruses.…”
Section: Introductionsupporting
confidence: 54%
“…Nerva et al (2017) presented strong evidence to show that a virus that infects an endophytic fungus could replicate in plants. Additionally, viroids have been shown to infect fungi efficiently (Wei et al, 2019). These findings further confirmed that some mycoviruses are close relatives to plant viruses.…”
Section: Introductionsupporting
confidence: 54%
“…1A). Conversely, the inocula used before (3) were monomeric RNAs with arbitrary termini flanked by vector sequences that may reduce/ abolish their infectivity (8,9) and that were not bioassayed in diagnostic host plants (3). In a second experiment, blocks of N. benthamiana were inoculated, instead of mechanically, by agroinfiltration (far more efficient) with Agrobacterium tumefaciens harboring plasmids for expressing dimeric head-to-tail transcripts of PSTVd, PLMVd, and ASBVd.…”
mentioning
confidence: 99%
“…This is our response to the letter by Serra et al (1), which questioned our recent paper (2) describing plant viroid infections in phytopathogenic fungi. In this study, full-length monomeric cDNA clones of seven plant viroid RNA genomes were produced using oligonucleotide synthesis (2). We opted for the monomeric version of viroid cDNA clone, considering that it requires shorter sequences for oligonucleotide synthesis and because of noting an article showing the infectivity of the monomeric cDNA clone of a viroid (3).…”
mentioning
confidence: 99%
“…We opted for the monomeric version of viroid cDNA clone, considering that it requires shorter sequences for oligonucleotide synthesis and because of noting an article showing the infectivity of the monomeric cDNA clone of a viroid (3). We constructed plasmid constructs for in vitro transcriptions by placing the viroid cDNA sequence immediately after a T7 promoter sequence and incorporating a restriction site (HindIII or SpeI) into the 3′ terminus (2). Due to the large number of samples, the infectivity of monomeric viroid cDNA transcripts was assayed by RT-PCR, and indeed, all of the RT-PCR products derived from the detection of viroid RNA accumulation in plants, yeast, and fungi inoculated with viroid RNA transcripts were verified by DNA sequencing.…”
mentioning
confidence: 99%
See 1 more Smart Citation